(untitled) (Cardiovascular Journal, 2022)
Background: Diabetes Mellitus (DM) is an established independent predictor of adverse prognosis in patients undergoing percutaneous coronary intervention (PCI) even with improvements in diabetes treatment and interventional techniques. The aim of this study was to compare long term post PCI outcome between diabetic and non-diabetic patients with ischemic heart disease (IHD). Method: The data was derived from a prospective observational study to evaluate the outcome after PCI in DM patients for 2 years. A total of 305 patients with IHD & DM were randomly selected and enrolled who underwent PCI from 2010 to 2013 in an urban cardiac hospital of Bangladesh. The study population were divided into two groups with group 1 consisting of patients with DM (n=108) and group 2 of patients without DM (n=197). After the PCI, all patients were followed up for 2 years. The incidences of bleeding, stent thrombosis, myocardial infarction (MI), stroke and repeat revascularization were compared. Results: Diabetic patients had significant adverse outcomes having MI, stroke & MACCE respectively following 1 year (p= 0.018, 0.036 & 0.017) and MI following 2 years (p= 0.013) compared to non-diabetic patients. However, in multivariate analysis, diabetes mellitus was not found to be an independent predictor for 1-year & 2-year adverse events following PCI [OR 1.016 (0.317-3.259) & p 0.979, after 1 year and 1.554 (0.087 – 27.902) & p 0.765, after 2 years]. Conclusions: The outcome of PCI after 1 year and 2 years among diabetic and non-diabetic subjects with IHD differed significantly in respect of MI, stroke & MACCE. But this study failed to identify diabetes mellitus as an independent risk factor for 1-year and 2-year adverse outcomes. Cardiovasc j 2022; 15(1): 5-12